Teaching Self-Efficacy at Primary Education in Greece - Terzi, Elpida (Innovare Journal of Education, 2024)
The parent quantitative research deals with teaching self-efficacy in primary education in Greece. The research aims to investigate teachers’ teaching self-efficacy in primary education in Greece. Specifically, an attempt is made to investigate how primary school teachers evaluate their level of self-efficacy regarding teaching tasks, managing disciplinary incidents in the classroom, and motivating students to be actively involved in the classroom and learning tasks, how the self-efficacy of primary education teachers from their educational experience and studies and what are the possible obstacles to the self-efficacy of these teachers. A sample of primary education teachers was recruited for this purpose. The research shows that the overall self-efficacy perception of teachers is exceptionally high with teachers considering themselves to be more effective in managing the classroom and implementing teaching strategies/educational approaches. Also, the self-efficacy of primary school teachers seems to be influenced by their educational experience and studies. Instead, it seems that teachers’ overall self-efficacy perception is related to factors such as the stress and pressure they experience, the degree of effectiveness they generally feel as individuals, and their goals.